Finding flowers in the dark: nectar-feeding bats integrate olfaction and echolocation while foraging for nectar - Gonzalez-Terrazas, Tania P. (R Soc Open Sci, 2016)
Nectar-feeding bats depend mainly on floral nectar to fulfil their energetic requirements. Chiropterophilous flowers generally present strong floral scents and provide conspicuous acoustic echoes to attract bats. While floral scents are assumed to attract bats over long distances, acoustic properties of flower structures may provide detailed information, thus supporting the localization of a flower at close ranges. So far, to our knowledge, there is no study trying to understand the relative importance as well as the combination of these generally coupled cues for detection (presence) and localization (exact position) of open flowers in nature. For a better comprehension of the significance of olfaction and echolocation in the foraging behaviour of nectar-feeding bats, we conducted two-choice experiments with Leptonycteris yerbabuenae. We tested the bats' behaviour in three experimental scenarios with different cues: (i) olfaction versus echolocation, (ii) echolocation versus echolocation and olfaction, and (iii) olfaction versus echolocation and olfaction. We used the floral scent of the bat-pollinated cactus Pachycereus pringlei as olfactory cue and an acrylic paraboloid as acoustic cue. Additionally, we recorded the echolocation behaviour of the bats and analysed the floral scent of P. pringlei. When decoupled cues were offered, bats displayed no preference in choice for any of the two cues. However, bats reacted first to and chose more often the coupled cues. All bats echolocated continuously and broadcast a long terminal group before a successful visit. The floral scent bouquet of P. pringlei is composed of 20 compounds, some of which (e.g. methyl benzoate) were already reported from chiropterophilous plants. Our investigation demonstrates for the first time to our knowledge, that nectar-feeding bats integrate over different sensory modes for detection and precise localization of open flowers. The combined information from olfactory and acoustic cues allows bats to forage more efficiently.